Metachronous infiltration of bone marrow due to breast cancer and multiple myeloma - Peker, Ahmet; Yarkıcı, Hakan; Uğur, Mehmet Can; Akar, Harun; Ceylan, Cengiz; Solakoğlu Kahraman, Dudu (The European Research Journal, 2018)
Multiple primary tumors are rarely seen in clinical practice. Cases of metastatic breast cancer associated with multiple myeloma were rare in the literature. It is believed that simultaneously observed bone marrow involvement due to breast cancer and multiple myeloma is sporadic. We present a 49-year-old female patient with metastatic breast cancer who developed multiple myeloma during breast cancer treatment.